2009
DOI: 10.1186/1471-2148-9-283
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic novelty in experimental hybrids is predicted by the genetic distance between species of cichlid fish

Abstract: BackgroundTransgressive segregation describes the occurrence of novel phenotypes in hybrids with extreme trait values not observed in either parental species. A previously experimentally untested prediction is that the amount of transgression increases with the genetic distance between hybridizing species. This follows from QTL studies suggesting that transgression is most commonly due to complementary gene action or epistasis, which become more frequent at larger genetic distances. This is because the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
175
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(193 citation statements)
references
References 74 publications
(73 reference statements)
12
175
1
2
Order By: Relevance
“…The ratio of the H, HG and G locus types was approximately equal to 1:2:1 following the genetic segregation of Mendelian law. This result differed from several reports on the abnormal genetic patterns of fish F 2 hybrids analyzed using molecular methods (Liu, 2003;Liu et al, 1998;Stelkens et al, 2009). Collectively, the backcross progeny and F 2 hybrids showed a degree of genetic recombination and segregation despite using only one nuclear marker.…”
Section: Maternal Inheritance and Genetic Recombinationcontrasting
confidence: 99%
“…The ratio of the H, HG and G locus types was approximately equal to 1:2:1 following the genetic segregation of Mendelian law. This result differed from several reports on the abnormal genetic patterns of fish F 2 hybrids analyzed using molecular methods (Liu, 2003;Liu et al, 1998;Stelkens et al, 2009). Collectively, the backcross progeny and F 2 hybrids showed a degree of genetic recombination and segregation despite using only one nuclear marker.…”
Section: Maternal Inheritance and Genetic Recombinationcontrasting
confidence: 99%
“…In addition, Tilapiine species (Oreochromis esculentus and Oreochromis niloticus) have also been reported to hybridize under experimental conditions (Welcomme 1966). Other GM studies regarding African cichlids (haplochromines) in lake Tanganyika reported pronounced shape variations in the F1 hybrids and concluded that hybridization among cichlids contribute significantly to morphological divergent (Stelkens et al 2009;Kerschbaumer and Sturmbauer 2011). The outstanding morph divergent exhibited by Victoria and Kyoga populations might therefore be an expression of introgression between Nile tilapia and its native relatives which might be one possible explanation why the native Tilapiines vanished.…”
Section: Discussionmentioning
confidence: 99%
“…This results in the occurrence of extreme trait values not observed in either parental taxon, including novel phenotypes, 27 ultimately increasing phenotypic variation in hybrid populations. Transgressive segregation has been shown to increase with increasing genetic distance between parental species 27 due to a rising number of fixed alleles with opposite effects. 28 Transgression in important traits is one means by which hybrids can invade and succeed in niches that are distinct from their parental species.…”
mentioning
confidence: 96%